2018
DOI: 10.3892/mmr.2018.8767
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation with ursolic acid ameliorates sepsis-induced acute kidney injury in a mouse model by inhibiting oxidative stress and inflammatory responses

Abstract: Ursolic acid (UA) as a multiple bioactive native compound has recently been demonstrated to treat sepsis in animal models. However, the beneficial effects of UA in sepsis-induced acute kidney injury (AKI) are not completely understood. In the present study, the effect of UA on sepsis-induced AKI in cecal ligation and puncture (CLP) surgery mice was investigated. Renal histomorphological analysis was performed by hematoxylin and eosin staining. The expression of inflammatory markers in the kidney of septic mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…(cranberry), Arctostaphylos uva-ursi (L.) Spreng (bearberry), Rhododendron hymenanthes Makino, Eriobotrya japonica, Rosemarinus officinalis, Calluna vulgaris, Eugenia jambolana and Ocimum sanctum, as well as in the wax-like protective coatings of fruits such as pears, apples and prunes [265]. UA has numerous biochemical and pharmacological effects including antiinflammatory, anti-oxidative, anti-proliferative, anti-atherosclerotic, anti-leukemic, anti-viral, and anti-diabetic effects [266][267][268][269][270][271][272]. It also exerts anti-cancer activities in ovarian, breast, gastric, prostate, lung, liver, bladder, pancreatic, and colorectal cancers [273][274][275][276][277][278][279][280][281].…”
Section: Ursolic Acid (Ua)mentioning
confidence: 99%
“…(cranberry), Arctostaphylos uva-ursi (L.) Spreng (bearberry), Rhododendron hymenanthes Makino, Eriobotrya japonica, Rosemarinus officinalis, Calluna vulgaris, Eugenia jambolana and Ocimum sanctum, as well as in the wax-like protective coatings of fruits such as pears, apples and prunes [265]. UA has numerous biochemical and pharmacological effects including antiinflammatory, anti-oxidative, anti-proliferative, anti-atherosclerotic, anti-leukemic, anti-viral, and anti-diabetic effects [266][267][268][269][270][271][272]. It also exerts anti-cancer activities in ovarian, breast, gastric, prostate, lung, liver, bladder, pancreatic, and colorectal cancers [273][274][275][276][277][278][279][280][281].…”
Section: Ursolic Acid (Ua)mentioning
confidence: 99%
“…Other anti-inflammatory and antioxidant actions of UA were in the mouse model of allergic asthma [141], cigarette smoke-induced emphysema in rats as chronic obstructive pulmonary disease (COPD) [142], and the LPS-induced lung injury in mice [143]. The 2,4,6-trinitrobenzenesulfonic acid- (TNBS-) induced colitis (colon shortening and myeloperoxidase (MPO) activity) model in the mouse model [144]; sepsis-induced acute kidney injury via inhibition of ROS and inflammatory cytokines, including TNF- α , IL-1 β , and IL-6 in the kidney from septic mice [145]; sepsis induced in rats by cecal ligation and puncture [146]; LPS-induced acute inflammation model [147]; and various other multiple mechanisms including NF- κ B and STAT3 inhibition [148] have been demonstrated. All these data support the anti-inflammatory mechanisms through inhibition of key inflammatory cytokines, COX and iNOS expressions, and antioxidant mechanisms including the activation of the Nrf2 pathway.…”
Section: General Antioxidant and Anti-inflammatory Effects Of Uamentioning
confidence: 99%
“…As an example, one study found that ursolic acid, one of the compounds in bearberry leaf extract, was able to ameliorate acute kidney injury associated with sepsis in mice. 24 A thorough review of the potential impact of each of these supplements on the patient's clinical presentation is beyond the scope of this work.…”
Section: Resultsmentioning
confidence: 99%
“…While the prevalence of CD is approximated to be one percent of the American population, it can be as high as four percent in those with cryptogenic transaminase elevation. 2,24 It has been demonstrated that patients with unexplained infertility, recurrent miscarriage or IUGR have a respective 5-, 6-or 8-fold risk of being afflicted by CD compared to the general population. 25 Additionally, patients with these reproductive disorders often do not present with the classic symptomology of CD.…”
Section: Discussionmentioning
confidence: 99%